Elevated Serum Levels of Progranulin and Soluble Vascular Cell Adhesion Molecule-1 in Patients with COVID-19 - Yao S (Dove Medical Press, 2021)
Shifei Yao,1,2 Nanning Luo,1,2 Jiaoyang Liu,1,2 He Zha,1 Yuanhang Ai,1,2 Juan Luo,1,2 Shi Shi,3 Kaifeng Wu1,2 1Department of Laboratory Medicine, Zunyi Medical University Third Affiliated Hospital/The First People’s Hospital of Zunyi, Zunyi, 563000, Guizhou, People’s Republic of China; 2Scientific Research Center, Zunyi Medical University Third Affiliated Hospital/The First People’s Hospital of Zunyi, Zunyi, 563000, Guizhou, People’s Republic of China; 3Department of Laboratory Medicine, The Fourth People’s Hospital of Zunyi, Zunyi, 563000, Guizhou, People’s Republic of ChinaCorrespondence: Kaifeng WuDepartment of Laboratory Medicine/Scientific Research Center, Zunyi Medical University Third Affiliated Hospital/The First People’s Hospital of Zunyi, Zunyi, 563000, Guizhou, People’s Republic of ChinaTel +86 85123116548Email kiphoonwu@126.comBackground: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is associated with the angiocentric inflammation and angiogenesis, yet the molecules involved in this process remain to be determined.Methods: We did a cross-sectional study of a cohort of patients with COVID-19 in Zunyi, China between February 1 and March 30, 2020. Serum concentrations of PGRN were determined by enzyme-linked immunosorbent assay in patients with COVID-19 at hospital admission and at discharge. In parallel, the serum levels of soluble adhesion molecules, vascular cell adhesion molecule-1 (sVCAM-1), intercellular adhesion molecule-1 (sICAM-1), P-selectin (sP-selectin), and E-selectin (sE-selectin) were assayed by a human adhesion molecule multiplex kit. The association between serum PGRN levels and other laboratory test results was analyzed by Spearman correlation analysis.Results: At baseline, the median serum PGRN levels in patients with COVID-19 were 94.8 ng/mL [interquartile range (IQR): 66.6– 119.6 ng/mL], which was significantly elevated compared with those in healthy controls (46.3 ng/mL, IQR: 41.8– 55.6 ng/mL). Moreover, the median serum sVCAM-1 levels were significantly higher in COVID-19 patients (1396.0 ng/mL, IQR: 1019.1– 1774.8 ng/mL) than those in healthy controls (612.4 ng/mL, IQR: 466.4– 689.3 ng/mL). However, the levels of sICAM-1, sP-selectin, and sE-selectin were not significantly elevated in patients with COVID-19 when compared to healthy controls. Further analysis showed that serum PGRN levels were significantly positively associated with sVCAM-1 (r= 0.675, P= 0.008) and inversely with sICAM-1 (r= − 0.609, P= 0.021) and aspartate aminotransferase levels (r= − 0.560, P= 0.037) in patients with COVID-19 at hospital admission. In COVID-19 patients, serum PGRN and sVCAM-1 levels fell significantly after successful treatment.Conclusion: The present study demonstrates elevated serum PGRN and sVCAM-1 levels in patients with COVID-19, which may provide clues as to the mechanisms underlying the pathogenesis of COVID-19. Further studies are warranted to evaluate the potential of PGRN and sVCAM-1 as biomarkers and investigate their role in the pathogenesis of COVID-19.Keywords: COVID-19, PGRN, soluble adhesion molecules, pathogenesis, biomarker